A post-ophiolitic plutonism record in the Central-East Iranian Microcontinent: Evidence for Pre-Eocene age of Neo-Tethys subduction - Marzieh Ghadirpour; Ghodrat Torabi; Nargess Shirdashtzadeh; Thomas C. Meisel; Tomoaki Morishita (Journal of African Earth Sciences, 2025)

Forearc magmatism in the Pannonian basin recorded by metasomatised skarnoid xenoliths in Pliocene basalt (Novohrad-Gemer Volcanic Field, Slovakia) - Luca Reato; Monika Huraiová; Lukáš Ackerman; Jana Ďurišová; Monika Horschinegg; Patrik Konečný; Thomas C. Meisel; Vratislav Hurai (Lithos, 2024)

Green and blue infrastructure as model system for emissions of technology-critical elements - Simone Trimmel; Philipp Spörl; Daniela Haluza; Nagi Lashin; Thomas C. Meisel; Ulrike Pitha; Thomas Prohaska; Markus Puschenreiter; Elmar Rückert; Bernhard Spangl; Dominik Wiedenhofer; Johanna Irrgeher (Science of The Total Environment, 2024)

Subduction zone-related metasomatism of Devonian oceanic lithosphere: Evidence from mineralogical, geochemical, and O-H-Sr isotope characteristics of amphibole-bearing peridotites of the Sowie Mountain Block (SW Poland) - Ahmed H. Ahmed; Mohamed M. Hamdy; Thomas C. Meisel (Lithos, 2024)

OpenWorkFlow—Development of an open-source synthesis-platform for safety investigations in the site selection process - Christoph Lehmann; Lars Bilke; Jörg Buchwald; Nico Graebling; Norbert Grunwald; Julian Heinze; Tobias Meisel; Renchao Lu; Dmitri Naumov; Karsten Rink; Ozan Özgür Sen; Philipp Selzer; et al. (Grundwasser, 2024)
The identification of appropriate locations for secure nuclear waste disposal, a crucial aspect of Germany’s nuclear phase-out strategy (StandAG 2017), remains a significant scientific, technical, and political challenge worldwide. The selection and safety assessment of sites demand extensive applications of numerical methods. The OpenWorkFlow project, initiated by Bundesgesellschaft für Endlagerung (BGE), develops a new, open synthesis platform to virtualise repository systems. The simulation platform will evaluate far-field and near-field processes, supporting the site selection process first and the geotechnical design of repository systems later on. The project’s development philosophy adheres to the principles of continuity and innovation. Through continuous scientific development, the OpenWorkFlow platform will remain at the forefront of science and technology. Furthermore, as a digital platform, OpenWorkFlow employs up-to-date IT methods and constantly evolving software concepts. As its name suggests, OpenWorkFlow (OWF) is an open platform, developed on the basis of FAIR principles as an open-source project, inviting community participation. This paper primarily focuses on the technical aspects of OWF, with only a brief discussion of conceptual principles and modelling methods. In the second part of the manuscript, demonstration examples from different scales are presented to illustrate the current technical status of OWF and to emphasize the requirement for further development.

Future renewable energy targets in the EU: Impacts on the German transport - Danial Esmaeili Aliabadi; Katrina Chan; Niklas Wulff; Kathleen Meisel; Matthias Jordan; Ines Österle; Thomas Pregger; Daniela Thrän (Transportation Research Part D: Transport and Environment, 2023)

To Waste or Not to Waste: Questioning Potential Health Risks of Micro- and Nanoplastics with a Focus on Their Ingestion and Potential Carcinogenicity - Elisabeth S. Gruber; Vanessa Stadlbauer; Verena Pichler; Katharina Resch-Fauster; Andrea Todorovic; Thomas C. Meisel; Sibylle Trawoeger; Oldamur Hollóczki; Suzanne D. Turner; Wolfgang Wadsak; A. Dick Vethaak; Lukas Kenner (Exposure and Health, 2023)
Micro- and nanoplastics (MNPs) are recognized as emerging contaminants, especially in food, with unknown health significance. MNPs passing through the gastrointestinal tract have been brought in context with disruption of the gut microbiome. Several molecular mechanisms have been described to facilitate tissue uptake of MNPs, which then are involved in local inflammatory and immune responses. Furthermore, MNPs can act as potential transporters (“vectors”) of contaminants and as chemosensitizers for toxic substances (“Trojan Horse effect”). In this review, we summarize current multidisciplinary knowledge of ingested MNPs and their potential adverse health effects. We discuss new insights into analytical and molecular modeling tools to help us better understand the local deposition and uptake of MNPs that might drive carcinogenic signaling. We present bioethical insights to basically re-consider the “culture of consumerism.” Finally, we map out prominent research questions in accordance with the Sustainable Development Goals of the United Nations.

Eco‐labeling of freight transport services: Design, evaluation, and research directions - Thomas Kirschstein; Arne Heinold; Martin Behnke; Frank Meisel; Christian Bierwirth (Journal of Industrial Ecology, 2022)
The idea of eco‐labeling is to provide customers with an easy‐to‐understand signal regarding the ecological impact of using a product or service. With this paper, we propose an eco‐labeling system for freight transportation. We discuss design options based on a common emission reporting standard and a related communication protocol. We further explain a procedure for deriving labels for shipments of goods and provide examples illustrating and evaluating the labeling process at selected land‐based freight transport services. Results indicate that eco‐labels can grade the environmental impact of a transport service reliably, even if heterogeneous goods are moved together. Finally, we outline challenges for future research associated with eco‐labeling in freight transportation markets.

Active biomonitoring of palladium, platinum, and rhodium emissions from road traffic using transplanted moss - Terhi Suoranta; Matti Niemelä; Jarmo Poikolainen; Juha Piispanen; Syed Nadeem Hussain Bokhari; Thomas Meisel; Paavo Perämäki (Environmental Science and Pollution Research, 2016)

Source components and magmatic processes in the genesis of Miocene to Quaternary lavas in western Turkey: constraints from HSE distribution and Hf–Pb–Os isotopes - Ercan Aldanmaz; Megan Pickard; Thomas Meisel; Şafak Altunkaynak; Kaan Sayıt; Pınar Şen; Barry B. Hanan; Tanya Furman (Contributions to Mineralogy and Petrology, 2015)

Origin of primary PGM assemblage in сhromitite from a mantle tectonite at Harold’s Grave (Shetland Ophiolite Complex, Scotland) - Inna Yu. Badanina; Kreshimir N. Malitch; Richard A. Lord; Thomas C. Meisel (Mineralogy and Petrology, 2013)

Inadequate cytoplasmatic calcium signals in alveolar macrophages after cardiac surgery - Katharina Berger; Michael Sander; Anke Kohlar; Christian Meisel; Wolfgang Konertz; Thomas Volk (Inflammation Research, 2010)

Petrology of Al- and Cr-rich ophiolitic chromitites from the Muğla, SW Turkey: implications from composition of chromite, solid inclusions of platinum-group mineral, silicate, and base-metal mineral, and Os-isotope geochemistry - İbrahim Uysal; Mahmud Tarkian; M. Burhan Sadiklar; Federica Zaccarini; Thomas Meisel; Giorgio Garuti; Stefanie Heidrich (Contributions to Mineralogy and Petrology, 2009)

Synthesis of PGE sulfide standards for laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) - Cora C. Wohlgemuth-Ueberwasser; Chris Ballhaus; Jasper Berndt; Vaida Stotter née Paliulionyte; Thomas Meisel (Contributions to Mineralogy and Petrology, 2007)

Association of MDR1 genotypes with susceptibility to colorectal cancer in older non-smokers - Elena Osswald; Andreas Johne; Gabriele Laschinski; Farhad Arjomand-Nahad; Uwe Malzahn; Julia Kirchheiner; Thomas Gerloff; Christian Meisel; Przemyslaw M. Mrozikiewicz; Jury Chernov; Ivar Roots; Karla Köpke (European Journal of Clinical Pharmacology, 2006)

Boron metasomatism and behaviour of rare earth elements during formation of tourmaline rocks in the eastern Arunta Inlier, central Australia - Johann G. Raith; Nina Riemer, ne Schner; Thomas Meisel (Contributions to Mineralogy and Petrology, 2004)